Economic and spatial determinants of interregional migration in Kazakhstan - Alisher Aldashev; Barbara Dietz (Institute for the Study of Labor (IZA), 2012)
In this paper we analyze economic and spatial determinants of interregional migration in Kazakhstan using quarterly panel data on region to region migration in 2008-2010. In line with traditional economic theory we find that migration is determined by economic factors, first of all income: People are more likely to leave regions where incomes are low and more likely to move to regions with a higher income level. As predicted by gravity arguments, mobility is larger between more populated regions. Furthermore, distance has a strong negative impact on migration, indicating high migration related costs and risks. Assuming that high migration costs are caused by poor infrastructure, investments in public and social infrastructure should facilitate regional income convergence in Kazakhstan and improve living standards in depressed regions.
urn:nbn:de:101:1-201203145575
Keywords: J61; P36; R23; 330; interregional migration; Kazakhstan; gravity model; Binnenwanderung; Regionale Einkommensverteilung; Gravitationsmodell; Kasachstan